The association between skin auto-fluorescence of palmoplantar sites and microvascular complications in Asian patients with type 2 diabetes mellitus - Jong Jin Kim (Nature Portfolio, 2018)
Abstract Skin auto-fluorescence (SAF) has generated broad interest about the prospects for non-invasive advanced glycation end product assessment and its direct interplay with the development of microvascular complications, but clinical application of the existing SAF measuring of non-palmoplantar sites in non-Caucasian subjects with dark skin type is still controversial. Here, we tested the diabetic complication screening performance of a novel SAF measuring system in Asian type 2 diabetes mellitus (T2DM) subjects. A total of 166 Korean patients with T2DM were enrolled in this study and palmoplantar SAF was measured by a newly developed transmission-geometry noninvasive optical system. We found that transmitted SAF values of palmoplantar sites, 1st dorsal interossei muscles of the hand, in a complication group were significantly higher than in a non-complication group while no differences were observed between the two groups in reflected SAF of non-palmoplantar sites. The transmitted SAF values of palmoplantar sites were dramatically increased in subjects with multiple complications and were tightly correlated with the duration of microvascular complications. In conclusion, the SAF measurement in the palmoplantar sites with a non-invasive transmission-geometry optical system provided better microvascular complication screening performance compared to the SAF measurement of non-palmoplantar sites specifically in Asian T2DM subjects.